OPERATIONAL AUDIT FROM THE PROCEDURES PROVIDING LOAN CREDIT FOR PREVENTING PROBLEMS CREDIT - RIKA HENDA SAFITRI; ABU KOSIM; MUHAMMAD NOPRI ISMANDA (Universitas Pamulang, 2018)
The purpose of this research is to know the procedure of giving working capital loan at Bank Sumsel Babel, to know whether the procedure of Working Capital Credit at Bank Sumsel Babel has been run in accordance with prevailing regulation in Bank Sumsel Babel, and also effort to prevent problem loans through operational audit. The research method used in this paper is descriptive analysis with data collection techniques in the form of observation and interview with Credit Division Bank Sumsel Babel. The results of this study indicate that from the five stages in the provision of working capital loans, there are several findings that exist at the stage of credit analysis and in the credit supervision stage. In the credit analysis phase of credit application instrument documents (PAK) in the form of MPK and FIP is not prepared in accordance with the guidance book of credit (BPP) of Bank Sumsel Babel. In the credit supervision stage, credit analyst of Bank Sumsel Babel does not compose FRP where the document is an important document to monitor the progress of the debtor in terms of future business prospects. The weakness has a significant impact on the provision of Bank Sumsel Babel where the weakness can lead to the risk of bad debts as a result of the wrong rating of the working capital creditors of Bank Sumsel Babel.